Antifouling coating of cellulose acetate thin films with polysaccharide multilayers. (13th February 2015) - Mohan, Tamilselvan; Kargl, Rupert; Tradt, Karin Eva; Kulterer, Martin R.; Braćić, Matej; Hribernik, Silvo; Stana-Kleinschek, Karin; Ribitsch, Volker
Highlights: Manufacturing of partially and fully deacetylated cellulose acetate thin films. Tuning of film thickness, surface composition, wettability and morphology. Correlation of alternating change in structural self-assembly, wettability and layer thickness. Successful removal of the multilayer coatings using HCl/NaCl solutions. Abstract: In this investigation, partially deacetylated cellulose acetate (DCA) thin films were prepared and modified with hydrophilic polysaccharides with the layer-by-layer (LbL) technique. As polysaccharides, chitosan (CHI) and carboxymethyl cellulose (CMC) were used. DCA thin films were manufactured by exposing spin coated cellulose acetate to potassium hydroxide solutions for various times. The deacetylation process was monitored by attenuated total reflectance-infrared spectroscopy, film thickness and static water contact angle measurements. A maximum of three bilayers was created from the alternating deposition of CHI and CMC on the DCA films under two different conditions namely constant ionic strengths and varying pH values of the CMC solutions. Precoatings of CMC at pH 2 were used as a base layer. The sequential deposition of CMC and CHI was investigated with a quartz crystal microbalance with dissipation, film thickness, static water contact angle and atomic force microscopy (AFM) measurements. The versatility and applicability of the developed functional coatings was shown by removing the multilayers by rinsing with mixtures containing HCl/NaCl. The developed LbL coatings are used for studying the fouling behavior of bovine serum albumin (BSA).